PENGARUH AUDIT COMPLEXITY, OWNERSHIP CONCENTRATION, DAN FINANCIAL DISTRESS TERHADAP AUDIT REPORT LAG (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFATAR DI BURSA EFEK INDONESIA PERIODE 2017- 2022) - Suci Putri Maryani; Asih Handayani (Publika Citra Media, 2024)
This research aims to determine the effect of audit complexity, ownership concentration and financial distress on Audit report lag in property and real estate sector companies listed on the Indonesian stock exchange in 2027-2022. The research method used is a quantitative method. The population in this study was 78 property and real estate companies listed on the Indonesian stock exchange in 2017 - 2022. The sample in this study was 16 companies. A total of 96 financial report data using the purposive sampling method as a sampling technique. Hypothesis testing in this research uses panel data regression analysis using E Views software version 12. The research results show that simultaneously audit complexity, ownership concentration and financial distress influence Audit report lag. Meanwhile, audit complexity partially influences Audit report lag, but ownership concentration and financial distress do not influence Audit report lag.